PENERAPAN SEMBILAN PRINSIP PEMBELAJARAN ORANG DEWASA RAMP 2 FAME PADA PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR - Sih Dewanti, Sintha (Universitas Ahmad Dahlan, 2012)
This study aims to improve the learning outcomes of students of class X Accounting 1 SMK Muhammadiyah Wonosari on teaching mathematics subject flat wake. Improved learning outcomes intended in this study is the average value over 75 and increased in every cycle test performed on each end of the discussion of the basic competencies and increased the percentage absorption per basic competence from one cycle to the next cycle. Efforts to improve the learning outcomes apply 9 adult learning principles RAMP 2 FAME (Recency, appropriateness, Motivation, Primacy, 2 way communication, feedback, Active learning, learning Multi sense, Exercise. The study was Classroom Action Research (CAR) using a model of Kemmis & McTaggart. Subjects in this study were all students of class X Accounting 1 SMK Muhammadiyah Wonosari Academic Year 2011/2012. The object of this research is the implementation of learning mathematics by applying 9 adult learning principles RAMP 2 FAME. PTK is accomplished in two cycles, each cycle was implemented in three meetings. In each cycle, the first and second meetings held for the learning and the last meeting held on the test cycle or daily tests per basic competence. The instruments used in the data collection in this study was achievement test. The results showed that there was an increase in students class X Accounting 1 SMK Muhammadiyah Wonosari on the subject of flat wake up after the action by applying the 9 principles of adult learning RAMP 2 FAME. Improved student learning outcomes is evident from the increase in value of the average grade on each test cycles performed per basic competence. The average value of the class on the first cycle test is 66.68 increased to 76.19 in the second cycle, while the percentage of absorption increased from 45.16% in the first cycle to 51.61% in the second cycle. Key words: adult learning, RAMP 2 FAME, learning outcomes